The Professional Identity Development of Prospective Teachers Uses A Narrative Inquiry Approach - Lestari, Ambar Sri; Rosmayasari, Rosmayasari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study examines prospective teachers' identity development in facing various challenges in their professional practice. Using a qualitative research method with a narrative inquiry approach to explore the experience and self-development of prospective teachers in teaching practice Collecting data through observation and interviews and using Clandinin's three interpretive narrative analysis tools, namely: expanding, exploring, and retelling narratives in interpretive ways to change the text the field became reflected in the research discourse Four teacher candidates were recruited as participants and agreed to take part in the research. The findings of this study reflect the main themes in the framework of the professional needs of prospective teachers through self-development through professional learning communities and the practice of teaching skills. This research has implications for forming the identity of prospective teachers as professional agents who need to be strengthened by experience in teaching practice.